Putting choice in the spotlight to advance theory on organizational adaptation to technological discontinuities - William R. Carter (Organization Management Journal (OMJ), 2020)
Purpose - This paper aims to develop and argue for a new research path to advance theory on incumbent firm adaptation to discontinuous technological change. Integrating variance and process epistemologies, implications of distinguishing a firm's capacity to adapt from their adaptive choices are highlighted. Design/methodology/approach - The concepts and argument presented are based on an extensive review and synthesis of the literature on the phenomenon. Findings - Distinguishing resource-based capacity variables and behavioral-based choice variables can fuel progress in the literature on incumbent adaptation to technological changes. More attention is needed on the direct, proximate determinants of what occurs in the process of adaptation, e.g. the intermediate choices to adapt, the timing of adaptive actions and the selection of a means for adapting. Work must then associate specific choices with performance outcomes to complete both sides of the mediated cause-effect model connecting characteristics of the decision issue to performance. Originality/value - Most studies toward understanding how incumbent firms adapt to discontinuous technological innovation have used variance analyses to identify firm and technology characteristics that explain adaptation outcomes. Focusing on characteristics and content, however, does not adequately explain why or how firms adapt. Scholars thus continue to lament the lack of clear, practical theory. I contend one heretofore unaddressed reason for this dissatisfaction is that too much of the research base neglects the importance of understanding choices and the factors affecting them.
Keywords: 650; Technology adoption; Organizational adaptation; Strategic choice; Discontinuous technological innovation; Incumbent adaptation to technological change